Fully Active Nitrogen Energetic Chains Mg2(N5)2N2[Mg2(N5)2N2]n under Ambient Conditions. Issue 5 (25th March 2021) - Gao, Yang; Wang, Rui; Lei, Jiehong; Zhu, Yu; Li, Danhui; Zhang, Lei; Xie, Weiyu; Wang, Zhigang
Abstract: Pentazolate anion (cyclo‐N5 − ) is a high energy density unit that has been synthesized. However, how to make cyclo‐N5 − complexes stable under ambient condition, without the presence of nonenergetic components, such as H3 O + and NH4 +, has always been a challenge. In this work, a fully active nitrogen energetic chain Mg2 (N5 )2 N2 [Mg2 (N5 )2 N2 ] n (denoted as ANEC n, n ≥ 1) is reported, which has high nitrogen content up to 78%. More importantly, first‐principles calculations and molecular dynamics simulations confirm the stability of this structure without external supports. Further electronic structure analysis indicates that the charge transfer from Mg to cyclo‐N5 − leads to strong covalent bonds, which promotes the stability of cyclo‐N5 − in the chain structures. This finding can contribute to rational design and synthesis of novel high‐energy density materials. Abstract : Fully active nitrogen energetic chains Mg2 (N5 )2 N2 [Mg2 (N5 )2 N2 ] n ( n ≥ 1), which are metal‐cyclo‐N5 − complexes that do not require nonenergetic ions as support and are stable at ambient conditions, are discovered by using first‐principles method. Due to their high nitrogen content, they have the potential to be an environmentally friendly high energy density material.